First molecular diagnosis of the human pathogen Rickettsia raoultii and other spotted fever group rickettsiae in Sudanese ixodid ticks from domestic ruminants - Nagwa Eisawi; Jabbar Ahmed; Mohammed A. Bakheit; Dina A. Hassan; Mohammed O. Hussien; Abdel Rahim M. El Hussein (Veterinary Medicine and Science)
Abstract Background Rickettsial infections are often neglected and poorly recognized by physicians in many tropical and subtropical regions. Despite a number of recent reports describing rickettsial diseases in new locations and the discovery of new rickettsiae, medical science and research have largely neglected the diagnosis and antimicrobial treatment of rickettsial infections in subtropical and tropical areas; thus, much remains to be discovered. This study aimed to detect and characterize spotted fever group (SFG) rickettsiae in ixodid ticks infesting domestic ruminants in Khartoum State. Methods Polymerase chain reaction targeting both genes that encode for citrate synthase (gltA) and outer membrane protein (ompA) was performed for the presence of SFG rickettsia followed by sequence and phylogenetic analysis. Results Of the 202 ticks examined for the presence of SFG rickettsia, gltA gene was detected in 4 samples (2%). Furthermore, gltA‐positive samples were used to amplify the ompA gene, in which only two samples yielded positive results. Sequence and phylogenetic analysis of the positive samples revealed four different species of SFG rickettsiae: Rickettsia aeschlimannii, Rickettsia rhipicephali, Rickettsia massiliae and Rickettsia raoultii. Conclusions These results indicated the presence of SFG rickettsia in Sudanese ticks. This also indicates that humans have an opportunity to acquire these infections. It is important to keep in mind the need for careful consideration of rickettsial infections in individuals with a fever of unknown origin.